Development Of Employee Attendance Information System Using Quick Response Code In Bekasi City Education Office - Khaerudin, Muhammad; Sumantri, Asep; Supriatna, Engkos; Ritzkal, Ritzkal (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2022)
Attendance can be said as a sign of a presence which is an activity of Reporting in a company or government agency, except for the attendance system in the Bekasi city education office which generally still uses the finger print attendance system. Where this is still inefficient because the current situation still has to be completely limited by the effects of the covid-19 pandemic, therefore it is very necessary to implement an online attendance system development that can be used by employees in the Bekasi city education office. The purpose of this study is to develop an online attendance information system using the "Quick Response Code" where with the implementation of this online attendance system, employees can directly scan the Qr Code using an Android smartphone. The design of this online attendance system uses the Unifield Modeling Language (UML) method. The script editor used is Android studio and visual code. The results of making the development of this online attendance system in the form of an attendance system that can be done online so that the attendance process carried out by employees becomes easier and more effective to use.